Enhancement of single‑photon emission from nitrogen‑vacancy centers with TiN/(Al, Sc)N hyperbolic metamaterial. Issue 1 (12th December 2014) - Shalaginov, Mikhail Y.; Vorobyov, Vadim V.; Liu, Jing; Ferrera, Marcello; Akimov, Alexey V.; Lagutchev, Alexei; Smolyaninov, Andrey N.; Klimov, Vasily V.; Irudayaraj, Joseph; Kildishev, Alexander V.; Boltasseva, Alexandra; Shalaev, Vladimir M.
<x xml:space="preserve">Abstract</x> The broadband enhancement of single photon emission from nitrogen‐vacancy centers in nanodiamonds coupled to a planar multilayer metamaterial with hyperbolic dispersion is studied experimentally. The metamaterial is fabricated as an epitaxial metal/dielectric superlattice consisting of CMOS‐compatible ceramics: titanium nitride (TiN) and aluminum scandium nitride (AlxSc1‐xN). It is demonstrated that employing the metamaterial results in significant enhancement of collected single photon emission and reduction of the excited‐state lifetime. The results could have an impact on future CMOS‐compatible integrated quantum sources. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>